2012
DOI: 10.1002/etc.1925
|View full text |Cite
|
Sign up to set email alerts
|

TFA from HFO-1234yf: Accumulation and aquatic risk in terminal water bodies

Abstract: A next-generation mobile automobile air-conditioning (MAC) refrigerant, HFO-1234yf (CF(3) CF = CH(2)), is being developed with improved environmental characteristics. In the atmosphere, it ultimately forms trifluoroacetic acid (TFA(A); CF(3)COOH), which is subsequently scavenged by precipitation and deposited on land and water as trifluoroacetate (TFA; CF(3)COO(-)). Trifluoroacetate is environmentally stable and has the potential to accumulate in terminal water bodies, that is, aquatic systems receiving inflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Benesch et al (2002) showed that trifluoroacetic acid does not adversely affect the development of soil microbial communities and pool plant species in vernal ponds. Modeling studies by Luecken et al (2010) and Russell et al (2012) have concluded that levels of trifluoroacetic acid resulting from extended (50 years) use of HFO-1234yf would not represent a risk to ecosystems in the U.S. With respect to trifluoroacetic acid formation from the atmospheric degradation of hydrofluorochlorocarbons (HCFCs) and hydrofluorocarbons (HFCs) it has been concluded that ''trifluoroacetic acid from the degradation of HCFCs and HFCs will not result in environmental concentrations capable of significant ecosystem damage'' (WMO, 2007). The same conclusion is applicable for short-chain haloolefins.…”
Section: Formation Of Noxious or Toxic Degradation Productsmentioning
confidence: 99%
“…Benesch et al (2002) showed that trifluoroacetic acid does not adversely affect the development of soil microbial communities and pool plant species in vernal ponds. Modeling studies by Luecken et al (2010) and Russell et al (2012) have concluded that levels of trifluoroacetic acid resulting from extended (50 years) use of HFO-1234yf would not represent a risk to ecosystems in the U.S. With respect to trifluoroacetic acid formation from the atmospheric degradation of hydrofluorochlorocarbons (HCFCs) and hydrofluorocarbons (HFCs) it has been concluded that ''trifluoroacetic acid from the degradation of HCFCs and HFCs will not result in environmental concentrations capable of significant ecosystem damage'' (WMO, 2007). The same conclusion is applicable for short-chain haloolefins.…”
Section: Formation Of Noxious or Toxic Degradation Productsmentioning
confidence: 99%
“…However, a risk evaluation of HFC-1234yf as alternative refrigerant for North America predicted concentrations of trifluoroacetate to remain below levels that could impair water quality. 136,139 This must be seen in relation to the comparatively small quantities needed in the electrical industry. equipment is replaced by halogenated butyl rubber.…”
Section: Last Generation Of Insulation Gasesmentioning
confidence: 99%
“…Efficient venting of surface emissions into the free troposphere and rapid transport from the simulation domain is consistent with our finding that only about 17% of the HFO-1234yf emissions resulted in TFA deposition inside the domain. 10.1002/2014JD022058 Russell et al [2012] conducted a model study of the expected concentration of TFA in terminal bodies of water from HFO-1234yf emissions in the contiguous USA, using TFA deposition rates of Luecken et al [2010]. Russell et al found aquatic concentrations of 1 to 15 μg L −1 after 50 years of continuous emissions, with extreme concentrations of up to 50 to 200 μg L −1 in the Sonoran Desert of the southwestern USA.…”
Section: 1002/2014jd022058mentioning
confidence: 99%
“…Henne et al [2012] investigated TFA deposition rates and rainwater concentrations over Europe with two Lagrangian chemistry transport models, based on scenarios of future HFO-1234yf emissions in Europe. Russell et al [2012] conducted a model study to determine the concentration of TFA in terminal bodies of water in the contiguous USA, with TFA deposition rates from Luecken et al [2010]. Russell et al found that after 50 years of continuous emissions, aquatic concentrations of 1 to 15 μg L −1 could accumulate, with extreme concentrations of up to 50 to 200 μg L −1 in the arid southwestern USA.…”
Section: Introductionmentioning
confidence: 99%